Not a Child's Play - Oguntoye Jide (Rasmed Publications Ltd., 2004)
The book revolves round a boy called Dere Isape. He got involved in illicit affairs at his teen age. He found fun-seeking to be a common game , despite the preaching against it everywhere. It was when his parents were killed by AIDS that he realized that the game is not a child's play but a dangerous one, read more about what happens to Dere Isape.
Keywords: Juvenile Fiction / Realistic / AIDS